Merger and Acquisition Integration Ultra Micro State-Owned Enterprise (SOE) Holding: A Systematic Literature Review - Eko Susetyono; Dominicus Savio Priyarsono; Anggraini Sukmawati; Popong Nurhayati (Jurnal Aplikasi Bisnis dan Manajemen, 2026)
Background: This research is important because although the literature on mergers and acquisitions (M&A) has developed significantly at the global level, most of it still focuses on private and multinational companies in developed countries, while studies on state-owned enterprises (SOEs) in the ultra-micro sector in developing countries, including Indonesia, are still very limited. However, the post-merger integration (PMI) process is a crucial factor in determining the success of M&A, and existing research remains fragmented between financial, structural, and sociocultural perspectives. In the Indonesian context, the formation of the Ultra-Micro Holding Company (HUM), involving BRI, Pegadaian, and PNM, plays a strategic role in expanding financial inclusion, strengthening access to financing for SMEs, and improving SOE efficiency. Therefore, a systematic review of M&A integration in ultra-micro SOEs not only contributes theoretically to the development of management science and public policy but also has practical implications for regulators and management in ensuring the success of such policies.Purpose: This study focuses on the application of mergers and acquisitions with a Systematic Literature Review (SLR) of previous studies, where mergers and acquisitions are an organized and flexible process used to deal with problematic situations that require corrective measures.Design/methodology/approach: This study used a qualitative approach through a systematic literature review (SLR) using the PRISMA approach.Conclusion: The results of this review show that M&A research is still dominated by the context of private and multinational companies in developed countries, while studies on ultra-micro SOEs in Indonesia are very limited. A systematic analysis underscores the importance of managerial factors, communication, and sociocultural aspects in the success of post-merger integration (PMI). However, previous research is theoretically fragmented and methodologically limited. Thus, this study highlights a research gap that necessitates further in-depth examination of M&A integration strategies in ultra-micro SOEs in developing countries.Originality/value (State of the art): This study makes an original contribution through an innovative combination of Mergers and Acquisitions with a Systematic Literature Review (SLR) in the context of state-owned enterprise (SOE) holding companies in Indonesia. Using the PRISMA approach, this study provides an in-depth analysis of the formation of ultra-micro holding companies involving the integration of three major financial institutions. The multidimensional analytical framework developed encompasses research trends, impact evaluation, success factors, model comparisons, policy evaluation, and risk analysis, providing a holistic understanding of SOE transformation through the formation of holding companies. Practically and theoretically, this study provides a framework for practitioners and fills a gap in the literature on SOE transformation studies in developing countries. Keywords:  acquisition, merger, prisma, systematic literature review, ultra-micro